Nanodiamonds in polymer hybrid composites - Shamsuri, Ahmad Adlie (Scientific Archives, 2024)
Nanodiamonds are nano-sized particles of diamond. They are gaining prominence in the field of material science due to their unique properties, such as high surface area, excellent thermal conductivity, and superior mechanical strength. When incorporated into polymer matrices, nanodiamonds contribute significantly to the enhancement of the composite’s overall performance. This editorial article imparts findings from recent research articles on the role of nanodiamonds in polymer hybrid composites, focusing on the common types of polymer matrices and fillers used alongside nanodiamonds, the influence of nanodiamonds on composite properties, and the advantages of incorporating nanodiamonds.